Interes prawny w uzyskaniu zaświadczenia w świetle regulacji k.p.a. - Strzępek, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The conditions for obtaining a certificate on having a legal interest pose significant theoretical and practical problems. The divergences in views presented in the case law of administrative courts justify a closer look at this issue. It seems to be particularly important to determine whether the legal interest in obtaining the certificate is the same as the legal interest determining participation in administrative proceedings as a party. The answer in this case is not unambiguous due to the different nature of the institution of the certificate, and the conclusions contained in the study may contribute to further discussion in this respect.
Keywords: legal interest; certification; party to the proceedings